MENERAPKAN NILAI ISLAM DALAM PENGEMBANGAN MUTU PENDIDIKAN TERKAIT MANAJEMEN SUMBER DAYA MANUSIA - Handika, Handika; Saputra, Yogie Dwi (STIT Pringsewu, 2019)
Abstract Human resource management is a specialized management field that studies the relationships and roles of humans in an organization. Humans are workers who work in a company. One of the factors that can develop education is the existence of good and appropriate human resource management in accordance with Islamic values. With the existence of quality human resources will be able to influence the process and better progress in the field of education. Increasing human resources is becoming increasingly important for institutions that are used to gain better control through their own institutions. Institutions must show that they are able to provide quality education for students. For each institution, quality is the agenda and the main quality of improvement is the most important task. One of the things that must be considered in human resource management in Indonesia is to improve the quality of education with the aim of changing the institutions that operate it into a sincere team, without conflict and internal competition, to achieve a goal, namely for the betterment of education.The results of this study indicate that: Planning resources to improve the quality of education selection and orientation, as well as the placement of human resources in a professional manner. The implementation of resources is carried out through educational activities, training and development of human resources that play a role in improving the quality of quality education in accordance with Islamic values.